Renal Involvement in Children with Dengue Fever: A Study in Tertiary Care Hospital of Bangladesh. (7th January 2020) - Sultana, Azmeri; Rumana, Jubaida; Roy, Smrity; Sonia, Seikh Farzana; Rahat, Farhana; Parvin, Ruma; Afroze, Sharmin
Abstract : Background and Objective : Dengue has emerged globally as the most relevant viral infection transmitted by a mosquito bite and represents a major threat to public health. Dengue-related renal manifestations such as proteinuria, hematuria, acute kidney injury (AKI), and rhabdomyolysis are not uncommon, and acute kidney injury (AKI) is a serious complication of dengue fever. There is relatively few data on the renal manifestations of dengue fever in children. Hence, this study was conducted to evaluate the incidence, characteristics, and clinical outcome of dengue fever with renal manifestations. Method . This prospective cross sectional study was conducted in Dr. M R Khan Children Hospital and Institute of Child Health, Dhaka, over a period of 1 year from January 2018 to December 2018. The study was approved by the ethical committee of the institute. A total number of 316 patients were admitted with the diagnosis of dengue fever either NS1 positive or antibody IgM positive or both IgM and IgG positive. Data were collected in a structured questionnaire form and were analyzed by SPSS version 20.0. The disease severity was classified according to the World Health Organization criteria. Renal manifestations were divided into AKI groups using pRIFLE criteria. Proteinuria was defined as urinary protein >1+ (30 mg/dL) by dipstick test. Hematuria was defined as red blood cell (RBC) >5/ μ L in a fresh uncentrifuged urine specimen. Result . Among 316 dengue patients, thirty-one patients (9.8%) had renal involvement. Most of the patients (54.83%) with renal manifestations were aged between 1 and 5 years. A total of 14 patients were found to have proteinuria (4.4%). Nephrotic-range proteinuria was seen in only one patient (0.3%). AKI was defined by pRIFLE criteria and was seen in 13 patients (4.1%); among AKI 6 (46.15%) had risk, three patients (23.07%) had injury and 4 (30.7%) had failure and needed peritoneal dialysis. Death occurred in 3 patients (9.6%) in dengue with AKI who had failure. The incidence of renal manifestations (proteinuria, hematuria, and AKI) is as high as 9.8% among patients with dengue, and those with AKI had significant morbidity and mortality. Conclusion . Renal involvement in children with dengue is not uncommon. Dengue associated with AKI had significant mortality and morbidity.